2021
DOI: 10.1111/jan.14840
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the association between nursing staff and nursing‐sensitive outcomes in long‐term institutional care

Abstract: Aims To examine the association between type of nursing staff and nursing‐sensitive outcomes in long‐term institutional care. Design This systematic review included studies published in English, German, and Dutch between January 1997 and January 2020. Data sources The databases Medline (PubMed), CINAHL, PsycINFO, Embase, and the Cochrane Library were searched. Original quantitative studies were included. Review methods The Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) guidelines we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…RNs working in nursing homes are important because they are responsible for older adults’ health, safety, and quality of life. Higher RN hours have a positive effect on reducing pressure ulcers, preventing falls, reducing tube feeding, and improving residents’ activities of daily living (Courvoisier et al., 2018 ; Shin & Hyun, 2015 ; Tuinman et al., 2021 ). Moreover, RNs play an important role in communicating with families and other staff, and engaging in indirect treatment activities such as equipment and drug management (McCloskey et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNs working in nursing homes are important because they are responsible for older adults’ health, safety, and quality of life. Higher RN hours have a positive effect on reducing pressure ulcers, preventing falls, reducing tube feeding, and improving residents’ activities of daily living (Courvoisier et al., 2018 ; Shin & Hyun, 2015 ; Tuinman et al., 2021 ). Moreover, RNs play an important role in communicating with families and other staff, and engaging in indirect treatment activities such as equipment and drug management (McCloskey et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most prior studies examining the educational background of nursing home staff focus on the total amount of care provided by one type of staff, for example, registered nurses or certified nurse assistants, and do not consider the skills mix (e.g., the percentage of the total number of hours of care provided by registered nurses). The inconclusive findings of a recent systematic review ( Tuinman et al, 2021 ) on the association between type of nursing staff and nursing-sensitive outcomes in institutional long-term care do not allow one to make recommendations on "who should best perform which care." In most of these studies, no distinction is made between vocationally trained or baccalaureate-educated registered nurses, while their educational backgrounds differ substantially ( Tuinman et al, 2021 ).…”
Section: Dear Editormentioning
confidence: 99%
“…The inconclusive findings of a recent systematic review ( Tuinman et al, 2021 ) on the association between type of nursing staff and nursing-sensitive outcomes in institutional long-term care do not allow one to make recommendations on "who should best perform which care." In most of these studies, no distinction is made between vocationally trained or baccalaureate-educated registered nurses, while their educational backgrounds differ substantially ( Tuinman et al, 2021 ).…”
Section: Dear Editormentioning
confidence: 99%
“…A systematic review by Recio‐Saucedo et al (2018) reported that only two out of four studies found significant associations between missed care and patient falls. Tuinman et al (2021) reported mixed results on the relationship between staffing levels and patient falls. A more recent study by Nantsupawat et al (2022) reported higher numbers of patients per nurse were associated with higher missed care and increased adverse events; however, there was no significant association between missed care and patient falls.…”
Section: Introductionmentioning
confidence: 99%